Decision Support System Using AHP to Determine Appropriate Television Shows for Children - Fitriani, Wirda; Purwanto, Dedi; Chairani, Ananda (International Conference on Sciences Development and Technology, 2023)
This study offers a Decision Support System (DSS) that uses the Analytical Hierarchy Process (AHP) to help youngsters choose appropriate television programs. The system is intended to provide parents with a simple and easy-to-implement option for controlling their children's television viewing habits. Its goal is to keep youngsters from imitating unwanted behaviors and to protect them from the detrimental effects of television material. The proposed DSS delivers critical information to allow interactive decision-making, ensuring that users have easy access to the information they require and can make well-informed decisions. The AHP methodology, a decision-making strategy that incorporates pairwise evaluations of selection criteria and available program options, is used in the system's implementation. AHP is particularly successful in solving multi-criteria problems, allowing for the prioritization and ranking of choices based on the research criteria. This study highlights the importance of the DSS in assisting parents in making educated decisions about their children's television programming, resulting in a safer and more educational viewing environment.